Evaluasi dan Potensi Ekstrak Daun Kayu Manis (Cinnamomum burmannii) untuk Pengelolaan Kesehatan dan Pertumbuhan Ikan Lele (Clarias sp.) - Tanbiyaskur, Tanbiyaskur; Effendi, Irzal; Supriyono, Eddy; Novitasari, Septi Liana (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
Aeromonas hydrophila bacteria can cause Motile Aeromonas Septicemia (MAS) disease in catfish. The use of phytopharmaceuticals is carried out as an alternative for disease control in catfish. One of the materials that can be used is the cinnamon leaf plant. This study aims to test the effectiveness of the use of cinnamon leaf extract through feed as a control of Motile Aeromonas Septicemia (MAS) disease in catfish (Clarias sp.). The feeding treatment was given 14 days before the challenge test and 14 days after the challenge test. This research was carried out at the Aquaculture Laboratory and Experimental Pond, Aquaculture Study Program and Laboratory of Microbiology and Biotechnology of Fishery Products, Fishery Product Technology Study Program, Department of Fisheries, Faculty of Agriculture, Sriwijaya University. This study used a Complete Randomized Design with 4 treatments and 3 replicates which included positive control (K+) without cinnamon leaf extract and infected with A. hydrophila, (P1) cinnamon leaf extract 0.25% in feed and infected with A. hydrophila, (P2) cinnamon leaf extract 0.5% in feed and infected with A. hydrophila and (P3) cinnamon leaf extract 0.75% in feed and infected with A. hydrophila. The results showed that cinnamon leaf extract at a dose of 0.75% in feed was the best treatment with 100% catfish survival, absolute length growth of 2.67 cm, absolute weight growth of 8.73 g, average percentage of fish recovered 100%, as well as total leukocytes, hemoglobin, and water quality within the normal range. Key words: Aeromonas hydrophila, catfish, cinnamin leaf extract